A Retinoid X Receptor Agonist Directed to the Large Intestine Ameliorates T-Cell-Mediated Colitis in Mice - Matsumoto, Ryohtaroh; Takahashi, Daisuke; Watanabe, Masaki; Nakatani, Shunsuke; Takamura, Yuta; Kurosaki, Yuji; Kakuta, Hiroki; Hase, Koji (Frontiers in Pharmacology, 2021)
Retinoid X receptor (RXR) is a nuclear receptor that heterodimerizes with several nuclear receptors, thereby integrating ligand-mediated signals across the heterodimers. Synthetic RXR agonists have been developed to cure certain inflammatory diseases, including inflammatory bowel diseases (IBDs). However, pre-existing RXR agonists, which are readily absorbed in the upper intestine, cause considerable adverse effects such as hepatomegaly, hyperlipidemia, and hypothyroidism. To minimize the adverse effects, we have developed an RXR agonist NEt-3IB with less lipophilic and thus poorly absorptive properties. In this study, we evaluated the effect of NEt-3IB in an experimental colitis model induced by adoptive transfer of CD45RBhighCD4+ T cells into mice. Pharmacokinetics studies demonstrated that the major portion of NEt-3IB was successfully delivered to the large intestine after oral administration. Notably, NEt-3IB treatment suppressed the development of the T cell-mediated chronic colitis, as indicated by improvement of wasting symptoms, inflammatory infiltration, and mucosal hyperplasia. The protective effect of NEt-3IB was mediated by suppression of IFN-γ-producing Th1 cell expansion in the colon. In conclusion, the large intestine-directed RXR agonist—NEt-3IB—is considered a promising drug candidate for IBDs.